From the land of hibiscus : Koreans in Hawaiʻi, 1903-1950 - Chʻoe, Yŏng-ho, 1931- (University of Hawai'i Press, 2007)
In 1903, 102 Koreans migrated to Hawai'i in search of wealth and fortune-the first in their country's history to live in the Western world. Thousands followed. Most of them, however, found only hardship while working as sugar plantation laborers. Soon after their departure, Korea was colonized by Japan, and overnight they became "international orphans" with no government to protect them. Setting aside their original goal of bettering their own lives, these Korean immigrants redirected their energies to restoring their country's sovereignty, turning Hawai'i into a crucially important base of Korean nationalism. From the Land of Hibiscus traces the story of Koreans in Hawai'i from their first arrival to the eve of Korea's liberation in 1945. Using newly uncovered evidence, it challenges previously held ideas on the social origins of immigrants. It also examines their political background, the role of Christian churches in immigration, the image of Koreans as depicted in the media, and, above all, nationalist activities. Different approaches to waging the nationalist struggle uncover the causes of feuds that often bitterly divided the Korean community. Finally, the book provides the first in-depth studies of the nationalist activities of Syngman Rhee, the Korean National Association, and the United Korea Committee. Contributors: Yŏng-ho Ch'oe, Anne Soon Choi, Sun-Pyo Hong, Do-Hyung Kim, Lili M. Kim, Richard S. Kim, Brandon Palmer, Judy Van Zile, Mahn-Yŏl Yi